2015
DOI: 10.3390/molecules200611257
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling and Evaluation of Pharmacological Activities of Hypericum scabrum L.

Abstract: Phytochemical investigations of ethyl acetate-soluble part of the aerial part of Hypericum scabrum L. delivered eight pure phenolic compounds 1-8. The pure compounds were identified through physico-chemical, NMR (1D, 2D) and mass spectrometric studies as: 3-8′′-bisapigenin (1), quercetin (2), quercetin (7), (+)-catechin (8). Total polyphenolic compounds and total flavonoids contents were determined in the extract as 0.107 mg·mg of the dried extract, respectively. Antioxidant activity using DPPH free radical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 13 publications
2
18
0
2
Order By: Relevance
“…All of the parts of this plant are sources of fatty acids, especially essential fatty acids, as well as effective natural antioxidants [69]. It has been indicated that, its extract possess flavonoids, such as quercetin [70]; flavonoids act as antioxidants [71]. In confirmation of our results, administration of H. scabrum Ext in rats was shown to improve learning and memory and possess antioxidant activity [27].…”
Section: Discussionsupporting
confidence: 83%
“…All of the parts of this plant are sources of fatty acids, especially essential fatty acids, as well as effective natural antioxidants [69]. It has been indicated that, its extract possess flavonoids, such as quercetin [70]; flavonoids act as antioxidants [71]. In confirmation of our results, administration of H. scabrum Ext in rats was shown to improve learning and memory and possess antioxidant activity [27].…”
Section: Discussionsupporting
confidence: 83%
“…The structures of all isolated compounds were elucidated by analyzing their spectral data (MS, 1 H- and 13 C-NMR, including HMQC, HMBC and DEPT) and by comparison with published literature data. They were thus identified as 3,3′,4,4′-tetra- O -methylellagic acid [ 10 ], 3,3′-di- O -methylellagic acid [ 11 ], caffeic acid [ 12 ], quercetin [ 13 ], (+)-catechin [ 14 ], (–)-epicatechin [ 13 ], (–)-epigallocatechin [ 15 ], gallic acid [ 16 ], β-sitosterol-3- O -β- d -glucopyranoside [ 17 ] and corilagin [ 18 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme activity was measured using the PTP-1B (3-(3,5-dibromo-4-hydroxybenzoyl)-2-ethylbenzofuran-6-sulfonic acid-(4-(thiazol-2-ylsulfamyl)-phenyl)-amide) enzyme inhibition assay according to the literature [ 13 , 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Different phenolics have been reported in Hypericum species, including catechin, quercetin derivatives, phenolic acids, etc. [ 6 , 7 ], each of these compounds presenting specific chemical properties. In this work, we aimed to study the phytochemical profile and bioactivity of H .…”
Section: Introductionmentioning
confidence: 99%